CLINICAL TYPES (CLASSIFICATION) OF THE RIGHT VENTRICLE ARRHYTHMOGENIC DYSPLASIA: SPECIFICS OF DIAGNOSTICS AND MANAGEMENT - Yu. A. Lutokhina (Российский кардиологический журнал, 2018)
Aim. To classify established clinical types of the right ventricle arrhythmogenic dysplasia (RVAD) taken a variety of genetic and inflammatory mechanisms, and to analyze the specifics of differential diagnostics and management of the respective types.Material and methods. Main group consisted of 50 patients with evident (n=26), probable (n=13) and possible (n=11) RVAD diagnosis, mean age 38,1±14,6 y. o., males — 20 (40%), follow up time 13,5 [4; 34] months. Comparison group consisted of 58 patients with some of the RVAD criteria insufficient for evident diagnosis. All patients underwent ECG, Holter ECG 24 hours, EchoCG; in the main group additionally — DNA-diagnostics (n=46), cardiac MRI (n=44), high definition ECG (n=16), endomyocardial biopsy of the RV (n=2), autopsy (n=2). In comparison group, MRI was done in 32 patients, biopsy to 7, and in 1 case — autopsy.Results. Based upon the clinical data and specifics of the disease course, 4 types of established clinical RVAD were selected, that do not tend to overlap: latent  arrhythmic (50% patients), manifest arrhythmic (20%), RVAD with predominant biventricular chronic heart failure (CHF, 16%), and RVAD with non-compaction left ventricle myocardium (14%). The development of one or another type is based on genetic factors, as on comorbid myocarditis (in percent in the following, respectively). In diagnostics of the latent arrhythmic type (frequent right ventricle extrasystoly, VE and/or non-sustained right ventricular tachicardia, VT) the key role played female sex, syncopes in anamnesis (16%), family history of sudden death (12%), ECG-criteria and positive results of DNA diagnostics (24%). For manifest arrhythmic type (sustained VT) — sudden death family anamnesis (in 20%), MRIcriteria (enlarged RV with lower EF), ECG-criteria and positive DNA tests (50%). For RVAD with progressing CHF — sustained VT (50%), syncopes (37,5%), predominance of RV failure with its severely reduced EF (25,7±15,0%), major MRI- and ECG-criteria, decreased QRS-voltage and positive DNA test (38%). Comorbidity of RVAD and non-compaction myocardium differ by frequent VE, aggressive VT (57,1%), syncope (42,9%) and CHF with significantly lower than in DCMP EF LV. Mortality rate in I-IV types was, respectively, 0%, 10%, 25%, 14,3%, and relevant shocks in 8 of 13 (61,5%) patients with ICD.Conclusion. It is worthy to use the proposed RVAD classification in clinical practice to define the spectrum of diagnostical and management events and assess the individual patient prognosis.